Understanding German real estate markets - Just, Tobias; Maennig, Wolfgang (Springer, 2017)
In this book, experts discuss how German real estate values have remained stable throughout the financial crisis, even though transaction volumes have been very volatile since 2005. Consequently, risk-averse national and international investors have started to invest in virtually all German real estate asset classes. This book tries to answer what has made the German real estate markets more resilient to shocks than many European real estate markets by analyzing the economic, regulatory and demographic environment. In 30 well-structured chapters, experts from both the academic and professional world analyze structural and current issues of German real estate markets. Readers will get a deep understanding of what makes the German real estate market special and where potential opportunities and threats in Europe's largest real estate market exist.
Keywords: Real estate investment -- Germany.; Real estate business -- Germany.; Real property -- Germany.; Germany.; elektronické knihy; electronic books